A cross sectional study on the physical and functional health status of the elderly population in Kampung Tebakang Melayu, Serian - Ahmad Tirmizi, Jobli; Aly, Alias stephen Nah; Bawih Inu, Pu'un; ch'ng Li, Shyan; Lee, Heng Ai; Julian Ong Joo, Lian; Ooi Boon, Han; Ronald Tang, Hion; Siti Baiduri, Busrah; Widyaningsih, Zaini; Fei, Wong Poh (Universiti Malaysia Sarawak (UNIMAS), 2002)
A cross-sectional study on the physical and functional health status of the elderly population of Kampung Tebakang Melayu aged 60 years and above was carried out from the 2nd of September 2002 to the 18`h of October 2002 by the fourth year medical students of University Malaysia Sarawak (UNIMAS). 76 respondents were identified and universal sampling was employed. Data was collected through interviews using a semi-structured questionnaire. 69 out of the 76 respondents (90.8%) were able to complete the physical examination and investigations and analysis of the parameters were based on these respondents. The data obtained was analyzed using the SPSS programme. The results revealed that gender distribution among the elderly population was equal. 69.7% of the elderly were currently married, all with primary education and 39.5% of the males and 21.1% of the females were found to be still economically active. The household income of most of the respondents was RM 500 and above There was also a positive correlation between advancing age and the number of illness symptoms. 80% of the respondents attributed their illness symptoms to the ageing process. The most common diagnosed medical condition was hypertension. Results showed that there was a negative correlation between advancing age and the number of medical conditions diagnosed. A significantly less number of the old olds (aged 70 and above) were found to be taking prescribed medication or to have sought medical attention from a doctor within the past 6 months as compared to the young olds. 86.8% of the elderly were functionally independent according to the Barthel's Index and there was significant association between poor functional status and existing medical conditions. From the physical and biochemical examinations, it was found that 34.3% of the young olds and 25% of the old olds had four or more abnormal parameters. As a conclusion, the elderly population was found to be independent but in need of regular medical screening and treatment, especially for visual problems and chronic medical conditions. Also, a quarter of the elderly needed help to travel to distant places and thus community support is needed to provide assistance and transportation for them to go for medical treatment. From the results obtained, an intervention programme themed `Kenali Awal, Rawat Segera. Hidup Sihat' was held on 29"i of September 2002. The aim of the programme was to heighten the knowledge regarding ageing, elderly healthcare, importance of health screening and to create the awareness that ageing does not necessarily equate to ill-health.